Coaching is key to SME success: International business coach Peter Boolkah explains why the right coach can take your business to the next level. Issue 3 (1st April 2014) - Bell, Gareth
Abstract : Purpose: – The purpose of the paper is to provide an interview with Peter Boolkah. Design/methodology/approach: – The paper discusses some of the current issues within the coaching industry. Findings: – Boolkah answers questions on coaching philosophy, what attributes make a successful coach and how a business can make the most of a coach's expertise. Practical implications: – Provides insight and advice from a leading industry professional.